Kristijonas Donelaitis’ Fables and the Bible - Dilytė, Dalia (Senoji Lietuvos literatūra, 2014)
So far the reverberations of the Bible in Donelaitis’s fables have not been addressed in a more consistent manner. A closer look at the fables shows that four fables out of six are related with the Bible. Direct citations from the Bible and reminiscences of different nature have been found in the fables ‘Lapės ir gandro česnis’ (The Fox’s and the Stork’s Feast), ‘Rudikis jomarkininks’ (The Dog at a Fair), ‘Pasaka apie šūdvabalį’ (The Fable of the Dung Beetle), and ‘Aužuols gyrpelnys’ (Oak the Braggart). Research material makes it possible to state that there are more connections with the New Testament; as for the Old Testament, connections were found only with the Book of Ecclesiasticus, or the Wisdom of Sirach. Biblical echoes more often sound in the morals of Donelaitis’ fables. The use of citations or allusions of the Bible in the fables shapes the image of the author as a spiritual leader of the community.